2011
DOI: 10.1155/2011/252387
|View full text |Cite
|
Sign up to set email alerts
|

Human Liver Cells Expressing Albumin and Mesenchymal Characteristics Give Rise to Insulin-Producing Cells

Abstract: Activation of the pancreatic lineage in the liver has been suggested as a potential autologous cell replacement therapy for diabetic patients. Transcription factors-induced liver-to-pancreas reprogramming has been demonstrated in numerous species both in vivo and in vitro. However, human-derived liver cells capable of acquiring the alternate pancreatic repertoire have never been characterized. It is yet unknown whether hepatic-like stem cells or rather adult liver cells give rise to insulin-producing cells. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Rather, these cells originated from differentiated adult cells with distinct metabolic function that possess developmental plasticity. However, due to the mesenchymal nature of human liver cells that have undergone EMT in vitro , and the technical challenge to trace human‐derived cells, we cannot unequivocally suggest that the human liver cells, which are predisposed to TD, indeed originate from adult human pericentral liver cells.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Rather, these cells originated from differentiated adult cells with distinct metabolic function that possess developmental plasticity. However, due to the mesenchymal nature of human liver cells that have undergone EMT in vitro , and the technical challenge to trace human‐derived cells, we cannot unequivocally suggest that the human liver cells, which are predisposed to TD, indeed originate from adult human pericentral liver cells.…”
Section: Discussionmentioning
confidence: 91%
“…In in vitro culture, proliferating human liver cells undergo dedifferentiation and epithelial‐to‐mesenchymal transition . However, our data suggest that these primary cultures of proliferating human liver cells retain, at least partially, the heterogeneity in Wnt signaling, which is in vivo related to the liver zonation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Transplantation of the Pdx1 ‐treated liver cells under the kidney capsule of immunocompromised mice ameliorated hyperglycemia throughout the 2‐month study. Subsequently, the same group demonstrated, with lineage tracing, that the liver‐derived insulin‐secreting cells originated mainly from albumin‐positive cells 89 . In parallel, the ectopic expression of Nkx6.1 in human liver cells by in vitro adenoviral infection resulted in the activation of several pancreatic transcription factors and a modest increase in insulin expression 90 .…”
Section: Novel Strategies To Restore Insulin Productionmentioning
confidence: 94%
“…It has been demonstrated that insulin can regulate glucose metabolism by activating mTOR pathway [19], [20]. The liver is known to be important in regulating glucose metabolism in response to growth factors and insulin treatment [21], [22]. With the co-treatment of saffron and insulin, mTOR pathway improves the insulin sensitivity [23].…”
Section: Introductionmentioning
confidence: 99%